2022
DOI: 10.1038/s41598-022-22215-y
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive evaluation of polygenic score and genotype imputation performances of human SNP arrays in diverse populations

Abstract: Regardless of the overwhelming use of next-generation sequencing technologies, microarray-based genotyping combined with the imputation of untyped variants remains a cost-effective means to interrogate genetic variations across the human genome. This technology is widely used in genome-wide association studies (GWAS) at bio-bank scales, and more recently, in polygenic score (PGS) analysis to predict and stratify disease risk. Over the last decade, human genotyping arrays have undergone a tremendous growth in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This challenge led to emergence of the bioinformatics field, and it is now essential to have a biostatistician or an expert in data interpretation as a collaborator. Furthermore, artificial intelligence has the capacity to discover novel approaches to analyze biomarker and genomic data, equipping us with cutting-edge tools for predicting genes or epigenetic factors associated with performance traits and to address challenges associated with evaluating and understanding vast quantities of genomic and biomechanical data ( Nguyen et al, 2022 ). Moreover, the large quantity of data being generated fundamentally changes the validation process, which now necessitates both discovery and hypothesis testing.…”
Section: Discussionmentioning
confidence: 99%
“…This challenge led to emergence of the bioinformatics field, and it is now essential to have a biostatistician or an expert in data interpretation as a collaborator. Furthermore, artificial intelligence has the capacity to discover novel approaches to analyze biomarker and genomic data, equipping us with cutting-edge tools for predicting genes or epigenetic factors associated with performance traits and to address challenges associated with evaluating and understanding vast quantities of genomic and biomechanical data ( Nguyen et al, 2022 ). Moreover, the large quantity of data being generated fundamentally changes the validation process, which now necessitates both discovery and hypothesis testing.…”
Section: Discussionmentioning
confidence: 99%
“…Typically PGS have been developed in cohorts of genotyped individuals using a limited set of directly measured variants on a genotyping array, which has been imputed to higher genome coverage using reference panels [ 139 ]. Recent studies have shown that the choice of imputation panel and strategy can affect PGS accuracy [ 140 ], and the choice of genotyping array can be particularly important for underrepresented populations [ 141 ]. Ideally, the clinical use of PGS should combine common and rare variants [ 139 ], even if the improvements to risk-stratification at the population level may be limited [ 142 ].…”
Section: Analytic Challenges For Translation Of Polygenic Scoresmentioning
confidence: 99%
“…Moreover, rare SNPs (<1% MAF) are more sensitive to the choice of the imputation process ( Lencz et al 2018 , Shi et al 2018 ), but PRSs rely mainly on common SNPs. While some works examined factors in the imputation process that impact the quality of PRS, such as the genotyping platform, phasing, and imputation methods ( Chen et al 2020 , Thanh Nguyen et al 2022 ), there has been no systematic assessment of how different ethnic compositions of the imputation panel affect the accuracy of PRS risk prediction.…”
Section: Introductionmentioning
confidence: 99%